2011
DOI: 10.1375/twin.14.2.192
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships of Umbilical Venous Volume Flow, Birthweight and Placental Share in Monochorionic Twin Pregnancies With and Without Selective Intrauterine Growth Restriction

Abstract: This study was conducted to investigate the relationship among umbilical venous volume flow, birthweight and placental share in monochorionic twins with or without selective growth restriction. Having excluded cases complicated with twin-to-twin transfusion syndrome and one co-twin suffering intrauterine fetal death, a total of 51 monochorionic twin pregnancies were divided into two groups as with (group 1) and without (group 2) selective intrauterine growth restriction. Umbilical venous volume flow was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…A recent study of monochorionic twin gestations evaluated UV volume flow in cases with and without selective growth restriction. This study demonstrated that, in those cases with selective growth restriction, UV flow is significantly lower in the smaller twin than in the larger twin, and UV flow normalized by estimated fetal weight (mL/kg/min) is still greater in the larger twin.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study of monochorionic twin gestations evaluated UV volume flow in cases with and without selective growth restriction. This study demonstrated that, in those cases with selective growth restriction, UV flow is significantly lower in the smaller twin than in the larger twin, and UV flow normalized by estimated fetal weight (mL/kg/min) is still greater in the larger twin.…”
Section: Discussionmentioning
confidence: 88%
“…This is associated with the slowed growth rate of twins during late gestation when compared to the singleton growth rate [142]. The incidence of multiple births is increasing and this is largely attributed to the increase in availability of infertility treatment, such as ovulation induction [143,144]. Monochorionic twins (identical twins that share one placenta) have a much greater chance of being born IUGR than dichorionic twins (twins that do not share the same placenta) [145,146].…”
Section: Intrauterine Infection and Inflammation (Chorioamnionitis)mentioning
confidence: 99%
“…This is associated with the slowed growth rate of twins during late gestation when compared to the singleton growth rate [142]. The incidence of multiple births is increasing and this is largely attributed to the increase in availability of infertility treatment, such as ovulation induction [143,144]. Monochorionic twins (identical twins that share one placenta) have a much greater chance of being born IUGR than dichorionic twins (twins that do not share the same placenta) [145,146].…”
Section: Multiple Birthsmentioning
confidence: 99%